Old age in the aging Europe - Krajewski, Piotr (Studia Ecologiae et Bioethicae, 2010)
The development of relationships between young people and the generation of the grandparents must be accompanied by a sense of solidarity and the need to share experiences, especially in the family circle. In this way, young people are slowly gaining experience in finding a thread of understanding and creating relations with other people from the atomizing population. Mutual understanding and keeping good relations between the generations also prevents the isolation and marginalization of the older generation; then the young people do not see any interest to „help” them in this. Today we can observe with concern how the culture of the nations living with the present moment is getting exhausted and disappears because the individual gradually is losing its connection with family members and the roots of its own history. After all, the older people are able to offer invaluable assistance to young people, they can be and should be the trustees of the past and all these things in order to prevent a young generation from forgetting traditions, customs, art, religion, music, culture, and crafts of their fathers.